Calving Dynamics and the Potential Impact of Mélange Buttressing at the Western Calving Front of Thwaites Glacier, West Antarctica - Adrian Luckman (Journal of Geophysical Research: Earth Surface, 2024)
The western region of the wide Thwaites Glacier terminus is characterized by a near‐vertical calving front. The grounding line at this western calving front (WCF) rests on a relatively high ridge, behind which exists a reverse‐sloping bed; retreat of the grounding line into this over‐deepening basin could therefore expose deep calving faces that may be subject to ice‐cliff failure. Here, we use the 3D Helsinki Discrete Element Model to identify the factors that control the calving dynamics in this location. We then focus on the ability of mélange to influence these dynamics given the wide embayment in which Thwaites Glacier terminates. We find that calving along the WCF is currently influenced by ice flow across the grounding line and consequent longitudinal tensile stress and rift formation. Calving is slowed in simulations that are initiated with a highly constricted mélange, with a thicker mélange suppressing calving entirely. We liken the constrained simulations to a scenario in which mélange piles behind a large grounded iceberg. In a future which may see calving become a more dominant control on the retreat of Thwaites Glacier, this type of blockage will be necessary for robust force chains to develop and transmit resistive forces to the terminus. The ability of the mélange to hinder calving at this location will be determined by the presence and rigidity of binding land‐fast sea ice and iceberg keel depths. Therefore, it is necessary to represent calving, mélange and sea ice in a single framework to predict the fate of Thwaites Glacier.